Allah Gifts to the Prophets in the Generous Qur’an : Objective study Verses (49 Shura, 5 Maryam, 83 poets, 8 AlImran, 9 sad, 35 sad, 50 Maryam A model) - Mohammed, Essam Mahmoud; Khudeir, Ismael Mukhlif (International Journal of Psychosocial Rehabilitation, 2020)
Giving gifts and donations is an important aspect of noble social behavior in the Islamic religion, which reflects the importance of divine mercy in the Holy Quran. The importance of research is linked By the grace and honor of God for human beings, and to harness it from creatures and gifts that are not counted in the earth, heaven and spirit, saying : "If ye would count up the favours of Allah, never would ye be able to number them” (Surat Al-Nahl : 18), likewise God Almighty singled out prophets with many talents such as a gift Baby, brother’s gift, money gift, king’s mercy, and many other great gifts. The gift of the prophets before and after Islam may differ in the Qur’an.